Pengaruh Majalah Ilmiah Kampus Pengawasan terhadap Peningkatan Pengetahuan dan Sikap APIP terhadap Fraud, serta Citra Pusdiklatwas BPKP - Dian Setyawati; Amiruddin Saleh; Musa Hubeis (Jurnal Komunikasi Pembangunan, 2017)
APIP is an internal government supervisory agency with the strategic function, but its capabilities are still to be improved. Especially the auditor’s competence to prevent and detect fraud. Pusdiklatwas BPKP in supporting the mission of the organization and maintain also enhance the image of the organization, has published a scientific magazine Kampus Pengawasan (KP). The purpose of this study is (1) to test the effect of the use of media magazine KP to change knowledge and attitudes APIP about fraud, (2) test the effect of media usage Magazine KP to the image of the organization, (3) analyze the effect of the characteristics of the reader, the information needs, assess the effectiveness of magazines and selectivity to improve the knowledge and attitudes APIP about fraud and the organization's image. This research uses quasy experimental method with a pretest and posttest nonekuivalen group design. Respondents in this study were 80 auditors from the Inspektorat office throughout Indonesia who are following the training program in Pusdiklatwas BPKP. The research proves that the scientific magazine KP significantly influence the rising effect of the magazine in the form of knowledge and attitudes APIP about fraud but does not significantly affect the organization's image enhancement both image institution and the teacher's image. Other variables that contributed significantly affect the influence of the magazine is characteristic of the reader, the assessment of effectiveness and selectivity while the organization's image is affected by characteristic of the reader.